Redes sociais na Internet: as práticas educativas digitais do Instituto Federal do Pará - Campus Castanhal de 2004 a 2010 - Canto, João de Jesus Farias (2011)
Speaking of the news when they are happening, when experience is used and if it is not an easy task. However this paper will discuss issues related to social networking sites in order to contribute to research and education, especially regarding its use as an educational practice in IFPA – Campus Castanhal. This institution originated from the former Escola Agrotécnica Federal - Pará, which was part of an educational network. Agro-technical Schools, were established mostly in the interior regions of the country and have always lived on the banks of digital technologies, today with a very different reality. We talk about our experience in Campus Castanhal, discussed the use of social networks on the Internet by the campus community and the possibilities for use of images as educational practices and memory, this content often used in social networks.